TRANSDISCIPLINARY AND TRANSNATIONAL MANIFESTATIONS IN OJĀRS FELDBERGS' ART: THE CONCEPT OF BORDERS. - Kristberga, Laine (Culture Crossroads, 2022)
In this article the author examines the concepts of transdisciplinarity and transnationalism as methodological tools in art analysis. By applying these tools to the case study of Latvian artist Ojārs Feldbergs and addressing the concept of borders in his art, the author questions knowledge production systems, especially in terms of Western art discourse. The author doubts that in our hybrid globalised world it is still possible to look at artists and their oeuvre through a monoethnic perspective. It is important to be aware of parallel processes, intercultural encounters and sources of inspiration beyond the borders of one country or discipline. Yet, in doing so, the centre-periphery relationship should be addressed critically and the dictate of cultural metropolises as centres should be avoided. Given that Feldbergs' art cannot be seen as a constituent of isolated elements - object (sculpture), space (environment), time, spectatorship - but, indeed, as a complex whole, which is hybrid and synthesised, it is crucial to define Feldbergs' artistic strategies addressing the concept of borders - both physical and symbolic.